Resveratrol Mediates the Apoptosis of Triple Negative Breast Cancer Cells by Reducing POLD1 Expression - Liang, Zhi-Jie; Wan, Yan; Zhu, Dan-Dan; Wang, Meng-Xin; Jiang, Hong-Mian; Huang, Dong-Lin; Luo, Li-Feng; Chen, Mao-Jian; Yang, Wei-Ping; Li, Hong-Mian; Wei, Chang-Yuan (Frontiers in Oncology, 2021)
Resveratrol (RSV) is known to possess anticancer properties in many types of cancers like breast cancer, and POLD1 may be a potential target. However, the anticancer mechanism of RSV on triple negative breast cancer (TNBC) remains unclear. In the present study, the antitumor effects and mechanism of RSV on TNBC cells was analyzed by RNA sequencing (RNA-seq), which was then verified via cell counting kit-8 (CCK8), immunofluorescence, immunohistochemistry, Western Blot (WB), flow cytometry and hematoxylin-eosin (HE) staining. Consequently, it was found that the survival rate of MDA-MB-231 cells gradually decreased as RSV stimulation concentration increased. The RNA-seq analysis results demonstrated that genes affected by RSV stimulation were mainly involved in apoptosis and the p53 signaling pathway. Moreover, apoptosis of MDA-MB-231 cells induced by RSV was observed to be mainly mediated by POLD1. Under the stimulation of RSV, the expression levels of full length PARP1, PCNA and BCL-2 were found to be significantly reduced, and the expression level of Cleaved-PARP1 as well as Cleaved-Caspase3 increased significantly. Additionally, the mRNA expression of POLD1 was significantly reduced with the stimulation of RSV, and the protein expression level was also inhibited by RSV in a concentration-dependent manner. The prediction of domain interaction suggested that RSV may bind to at least 5 functional domains of the POLD1 protein (6s1m, 6s1n, 6s1o, 6tny and 6tnz). Furthermore, after RSV stimulation, the anti-apoptotic index (PCNA, BCL-2) of MDA-MB-231 cells was found to decrease while the apoptosis index (caspase3) increased. Moreover, the overexpression of POLD1 was observed to reduce RSV to MDA-MB-231 in view of its apoptotic effect on cells. The animal experimental results showed that RSV has a significant inhibitory effect on the growth of live tumors, while POLD1 overexpression can antagonize this inhibitory effect. This study’s findings reveal that RSV may promote the apoptosis of TNBC cells by reducing the expression of POLD1 to activate the apoptotic pathway, which may serve as a potential therapy for the treatment of TNBC.